Complementary medicine use by middle-aged and older women: personality, mood and anxiety factors. - Sarris, J; Goncalves, D; Robins Wahlin, T; Byrne, G (2011)
This study analysed NEO Five Factor Inventory (NEO-FFI) personality trait data in middle-aged and older Australian women and their CAM usage. Participants were women from the Longitudinal study of Ageing in Women (LAW study) aged 47 to 87 years (N = 419). Only the NEO-FFI trait of Openness was significantly correlated with cumulative CAM product use. Regression models revealed that number of specialists' consultations, number of CAM products used and reported level of physical and leisure activities were predictive of CAM therapy use; while age was predictive of CAM product use.